“They gotta understand why”: Teachers’ professional perceptions regarding the stimulation of academic motivation in upper secondary school - Tharaldsen, Kjersti Balle (Frontiers in Education, 2022)
In recognition of the need for more research on teachers’ perceptions of motivational work in the classroom, this study explores upper secondary school teachers’ perceptions of how to stimulate academic motivation among their students at a school in southwestern Norway. The data were gathered in three steps. The school’s primary teachers (n = 33) were interviewed by teacher champions (n = 17), that is, teachers that were team leaders for each of the school’s educational departments that were given a specific role in the research in terms of initial data collection. This was followed by two extended focus groups with the teacher champions and member checks for each group. The data were subjected to conventional content analyses using NVivo 12. Then a focus group was carried out with teacher coordinators (n=11) aiming to refine preliminary findings. A summative content analyses was carried out, followed by deductive category application. The findings indicate that teachers perceive class management and strategies for supporting students’ learning processes as well as key students as crucial for academic motivation. Three motivational strategies were developed. However, feedback and differentiated learning tasks, which are central aspects of motivational theories, received less emphasis. Further in-depth studies exploring concrete approaches to and the evaluating of using strategies for stimulating academic motivation are required.